Differential Expression Profile of Salivary oncomiRNAs among Smokeless Tobacco Users - AL-Rawi, Natheer H.; Rizvi, Zuha; Mkadmi, Sarra; Abu Kou, Rawan; Elmabrouk, Neibal; Alrashdan, Mohammad S.; Koippallil Gopalakrishnan, Aghila Rani (European Journal of Dentistry, 2023)
Objective The aim of this study was to evaluate the expression of selected salivary oncomiRNAs among smokeless tobacco users and nonsmokers.Materials and Methods Twenty-five subjects with chronic smokeless tobacco habit (> 1 year) and 25 nonsmokers were selected for this study. MicroRNA was extracted from saliva samples using the miRNeasy Kit (Qiagen, Hilden, Germany). The forward primers used in the reactions include hsa-miR-21-5p, hsa-miR-146a-3p, hsa-miR-155-3p, and hsa-miR-199a-3p. Relative expression of miRNAs was calculated using the 2-ΔΔCt method. Fold change is calculated by raising 2 to the power of the negative ΔΔCT value.Statistical Analysis Statistical analysis was carried out using GraphPad Prism 5 software. A p-value less than 0.05 was considered statistically significant.Results The four tested miRNAs were found overexpressed in saliva of subjects with smokeless tobacco habit when compared with saliva from nontobacco users. miR-21 expression was 3.74 ± 2.26 folds higher among subjects with smokeless tobacco habit compared to nontobacco users (p < 0.01). The expression for miR-146a (5.56 ± 8.3 folds; p < 0.05), miR-155 (8.06 ± 23.4 folds; p < 0.0001) and miR-199a (14.39 ± 30.3 folds; p < 0.05) was significantly higher among subjects with smokeless tobacco habit.Conclusion Smokeless tobacco leads to salivary overexpression of the miRs 21, 146a, 155, and 199a. Monitoring the levels of these four oncomiRs may provide insight about the future development of oral squamous cell carcinoma, especially in patients with smokeless tobacco habits.
Keywords: smokeless tobacco; miR-21; miR-146a; miR-155; miR-199a; oral cancer